More epigenetic hits than meets the eye: microRNAs and genes associated with the tumorigenesis of retinoblastoma - Reis, Adriana H.; Vargas, Fernando R.; Lemos, Bernardo (Frontiers in Genetics, 2012)
Retinoblastoma (RB), a childhood neoplasia of the retinoblasts, can occur unilaterally or bilaterally, with one or multiple foci per eye. RB is associated with somatic loss-of-function of both alleles of the tumor suppressor gene RB1. Hereditary forms emerge due to germline loss-of-function mutations in RB1 alleles. RB has long been the prototypic ‘‘model’’ cancer ever since Knudson’s ‘‘two-hit’’ hypothesis. However, a simple two-hit model for RB is challenged by an increasing number of studies documenting additional hits that contribute to RB development. Here we review the genetics and epigenetics of RB with a focus on the role of small noncoding RNAs (microRNAs) and on novel findings indicating the relevance of DNA methylation in the development and prognosis of this neoplasia. Studies point to an elaborated landscape of genetic and epigenetic complexity, in which a number of events and pahtways play crucial roles in the origin and prognosis of RB. These include roles for microRNAs, inprinted loci, and parent-of-origin contributions to RB1 regulation and RB progression. This complexity is also manifested in the structure of the RB1 locus itself: it includes numerous repetitive DNA segments and retrotransposon insertion elements, some of which are actively transcribed from the RB1 locus. Altogether, we conclude that RB1 loss of function represents the tip of an iceberg of events that determine RB development, progression, severity, and disease risk. Comprehensive assessment of personalized RB risk will require genetic and epigenetic evaluations beyond RB1 protein coding sequences.